2021
DOI: 10.3390/su13010364
|View full text |Cite
|
Sign up to set email alerts
|

Mobility Behaviour in View of the Impact of the COVID-19 Pandemic—Public Transport Users in Gdansk Case Study

Abstract: The COVID-19 pandemic, like an earthquake, shocked our civilization and is still having a devastating effect on our lives. Guaranteeing an appropriate level of safety in the conditions of an epidemic is a highly problematic issue due to the subjectivism of social individuals, their diverse attitudes, and past life experiences. Taking into account the World Health Organisation (WHO) guidelines regarding the pandemic, authorities all around the world have reacted by issuing the necessary sets of advice and legal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
134
1
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(181 citation statements)
references
References 76 publications
2
134
1
2
Order By: Relevance
“…A ten-country survey by Barbieri et al ( 2021 ) found that, while mobility was reduced across all transport modes, the decline was most pronounced for public transport and least pronounced for cars. Similarly, several other studies show that the share of car usage in the modal split has increased in several countries (Bucsky 2020 ; Eisenmann et al 2021 ; Molloy et al 2021 ; Przybylowski et al 2021 ).…”
Section: Ambiguous Sustainability Effects Of Individual Changementioning
confidence: 60%
“…A ten-country survey by Barbieri et al ( 2021 ) found that, while mobility was reduced across all transport modes, the decline was most pronounced for public transport and least pronounced for cars. Similarly, several other studies show that the share of car usage in the modal split has increased in several countries (Bucsky 2020 ; Eisenmann et al 2021 ; Molloy et al 2021 ; Przybylowski et al 2021 ).…”
Section: Ambiguous Sustainability Effects Of Individual Changementioning
confidence: 60%
“…Hence, it is essential to look at four key aspects: earlier travel patterns, lockdowns, transition stage, and adopting the new normal. Earlier studies have observed that such disruptions can catalyse the behavioural shifts towards more sustainable behaviour; however, curbing a return to pre-pandemic behaviours will require governments to make strict and responsible decisions [51].…”
Section: Discussionmentioning
confidence: 99%
“…As in many studies [5,6,17,18], the choice of transport mode and acceptable levels of vehicle occupancy are also influenced by the country of origin. Although the respondents who participated in this research belong to countries that are geographically close to each other, in each country different demographic factors affect this aspect differently.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic has had a major impact on the public passenger transport system [10], as it was identified as a high-risk environment for the spread of the virus [11][12][13][14]. Compared to private vehicles and other modes of transport [15][16][17], public transport was the most strongly affected [5,6,17,18], since conducting social distancing and providing the necessary materials for safe travel required a great deal of material and organizational resources [18].…”
Section: Transport and Covid-19mentioning
confidence: 99%